2018
DOI: 10.1111/apm.12791
|View full text |Cite
|
Sign up to set email alerts
|

Membrane‐active peptide PV3 efficiently eradicates multidrug‐resistant Pseudomonas aeruginosa in a mouse model of burn infection

Abstract: The aim of this study was to evaluate the topical bactericidal activity of peptide PV3 against a MDR isolate of Pseudomonas aeruginosa in a mouse model of burn infection. The structural analysis of PV3 by circular dichroism spectroscopy indicated a low peptide helical content in water, whereas a high helical content was observed in the presence of the more hydrophobic 50% (v/v) trifluoroethanol/water buffer. A confocal microscopy analysis indicated that the main action of PV3 occurred at the membrane of bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…In agreement with the current study, previous reports revealed rapid bactericidal activities of synthetic AMPs over tested antibiotics . It is worthwhile noting that a faster killing action of AMPs has unique advantages over traditional antibiotics such as limiting spread of infection, diminishing the likelihood of developing drug resistance, and reducing treatment duration …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In agreement with the current study, previous reports revealed rapid bactericidal activities of synthetic AMPs over tested antibiotics . It is worthwhile noting that a faster killing action of AMPs has unique advantages over traditional antibiotics such as limiting spread of infection, diminishing the likelihood of developing drug resistance, and reducing treatment duration …”
Section: Discussionsupporting
confidence: 92%
“…These fascinating peptides usually maintain common physicochemical characteristics. In general, AMPs consist of less than 50 amino acid residues, exhibit a positive net charge, and display an amphipathic nature . These characteristics are believed to be crucial for antimicrobial activity of AMPs .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is estimated that P. aeruginosa infection accounts for a higher mortality rate than burn shock and hypovolemia in burn care units. Considering the lethal effects of wound infection with multidrug‐resistant P. aeruginosa , the lack of effective therapeutic regimes as well as the frequency of bacterial infection in developing countries, novel, effective, and economic antimicrobial agents are urgently needed …”
Section: Introductionmentioning
confidence: 99%
“…These peptides strongly bind to negatively charged membranes and subsequently lyse them . The outer membrane of cancer cells contain negatively charged phosphatidylserine, which may contribute to the anticancer properties of AMPs . However, the utilization of native AMPs is limited, as their function is compromised in serum because of enzymatic degradation and binding to serum components .…”
Section: Introductionmentioning
confidence: 99%